The last major beam is lifted onto Sophia Gordon Hall after being signed by construction workers. Photo 084 - Loeb, Brian (Tufts Archival Research Center, 2008)
The last major beam is lifted onto Sophia Gordon Hall after being signed by construction workers. At the podium are Fisher and Trufant from Linbeck Construction, and Tufts Professor Brian Brenner.